Service quality and customer satisfaction in thermal tourism. Issue 1 (9th January 2017) - Silvestri, Cecilia; Aquilani, Barbara; Ruggieri, Alessandro
Abstract : Purpose: Satisfaction in the tourism sector is a highly sensitive subject, and customer satisfaction (CS) has a significant impact on the choice of destinations made by tourists and on the decision to recommend them to friends or acquaintances. The purpose of this paper is to give empirical evidence of the dimensions of service quality (technical, functional and company image (CI)) and their connections in the sector of thermal tourism. It also aims at investigating the CI, seeking to understand whether some of the technical and functional service quality variables play a role in determining it. Design/methodology/approach: An empirical survey was conducted by administering a structured research questionnaire in order to collect all necessary data, which was then elaborated to test the hypotheses using factor and multiple regression analyses. Findings: The results of the survey confirm the direct impact of service quality dimensions (technical, functional and CI) on CS also in the thermal sector when considered individually. Moreover, when the CI was analyzed further, relational quality was found to be dependent on thermal employees' capabilities, abilities, trustworthiness, availability, etc. Finally, when considered together, functional service quality and CI have a stronger effect on CS than technical service quality. Originality/value: The originality of the present research relies on the following: a further contribution to the so-called "European perspective" of service quality; the study of service quality dimensions (technical, functional and CI) in the thermal sector; and evidencing the link between thermal employee characteristics and the relational quality factor of the CI, demonstrating that many aspects of this construct need further empirical investigation, in the wellness sector.